Comparative Analysis of Kivy and Other Mobile Development Platforms (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper presents a comprehensive comparative analysis of Kivy, an open-source Python framework for developing multitouch applications, against other leading mobile development platforms such as React Native, Flutter, and Xamarin. The study aims to evaluate and contrast these platforms across various critical aspects, including development environment, programming language, ease of use, performance, community support, and flexibility. Kivy’s unique Pythonic approach is examined in the context of its suitability for rapid prototyping and cross-platform application development. Conversely, the paper also delves into the performance-oriented design of platforms like React Native and Flutter and the native integration capabilities of Xamarin. The analysis is grounded in a combination of qualitative assessments and quantitative data, including developer surveys, performance benchmarks, and case studies. This comparative study seeks to provide valuable insights for developers and organizations in making informed decisions about choosing the most appropriate mobile development platform based on their specific project requirements, resource availability, and long-term development goals.